SHIELD: Skull-shaped hemispheric implants enabling large-scale electrophysiology datasets in the mouse brain - Bennett, Corbett; Ouellette, Ben; Ramirez, Tamina K; Cahoon, Alex; Cabasco, Hannah; Browning, Yoni; Lakunina, Anna; Lynch, Galen F; McBride, Ethan G; Belski, Hannah; Gillis, Ryan; Grasso, Conor; et al. (Neuron (Cambridge, Mass.), 2024)
To understand the neural basis of behavior, it is essential to measure spiking dynamics across many interacting brain regions. Although new technologies, such as Neuropixels probes, facilitate multi-regional recordings, significant surgical and procedural hurdles remain for these experiments to achieve their full potential. Here, we describe skull-shaped hemispheric implants enabling large-scale electrophysiology datasets (SHIELD). These 3D-printed skull-replacement implants feature customizable insertion holes, allowing dozens of cortical and subcortical structures to be recorded in a single mouse using repeated multi-probe insertions over many days. We demonstrate the procedure's high success rate, biocompatibility, lack of adverse effects on behavior, and compatibility with imaging and optogenetics. To showcase SHIELD's scientific utility, we use multi-probe recordings to reveal novel insights into how alpha rhythms organize spiking activity across visual and sensorimotor networks. Overall, this method enables powerful, large-scale electrophysiological experiments for the study of distributed neural computation.